Upholding person-centred principles in the care plan. (2nd August 2019) - Ashurst, Adrian
Abstract : A personalised care plan is key to delivering good care to residents; therefore, care staff should be trained to carry out care assessments and draw up care plans. This month, Adrian Ashurst talks about how he trains carers to devise the care plan itself.